TARGETING DESIGN TO THE LUNGAND PULMONARY INTRACELLULAR STRUCTURE OF ENDOGENOUS GENE BY IRQ MODIFIED NANO CARRIER - Diky Mudhakir; Hidetaka Akita; Hideyoshi Harashima (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
TARGETING DESIGN TO THE LUNGAND PULMONARY INTRACELLULAR STRUCTURE OF ENDOGENOUS GENE BY IRQ MODIFIED NANO CARRIER. Inhibition of angiogenesis is a novel strategy for the treatment of lung cancer. For efficient therapy, vectors must firstly reach the target tissue and subsequently demonstrate an efficient intracellular targeting. In this study, we attempted to design a vector for in vivo pulmonary targeting which was able to deliver small interfering RibonucleicAcid (siRNA) for endogenous gene of angiogenesis in pulmonary endothelial cells. siRNA was condensed with polycation agent and encapsulated in lipidous nano carrier. To obtain high level of lung accumulation, we controlled the surface of nano-carrier by changing the length of Polyethylene glycol (PEG) moiety. These nano carriers showed prominent Ribonucleic acid interference (RNAi) effect, when luciferase gene was used as a target. In addition, an efficient transgene knockdown of Vascular Endothelial Growth Factor Receptor 1 (VEGFR1), a responsible gene of angiogenesis, can be obtained by the Instantaneous Respiratory Exchange Ratio (IRQ) modified nano carrier with the use of Stearyl-R8 (STR-R8) peptide, known as an endosomal membrane inducer. In conclusion, pulmonary targeting of nano carrier by encapsulating siRNA can be developed by controlling the PEG length and the structure of nano carrier for efficient intracellular targeting.